Genie genie genie - Fine, Anne (Egmont London, 2004)
Three stories of magical genies, far off lands and flying carpets! Jeanie finds a real genie to help her with a dull day at school. William's had a fight with his grandmother and needs a genie to cheer him up. And Hasan shows Toby round ancient Arabia ..